2017
DOI: 10.1093/trstmh/trx062
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of lymphatic filariasis among migrant workers in Peninsular Malaysia

Abstract: Malaysia is not endemic for Wuchereria bancrofti, but harbors the vectors for the parasite, thus the results showed that migrant workers should be monitored for this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…16 In a recent seroprevalence study among migrant workers in Malaysia, BLF Rapid was positive in 19.6% workers from India (10/51), 12.6% from Nepal (13/103), and 7.1% from Myanmar (1/14). 7 In conclusion, the present study showed that BLF Rapid test is a highly sensitive and specific test for detection of bancroftian filariasis in areas not endemic for O. volvulus or L. loa. The encouraging evaluation results and the field-applicability make the test a potential diagnostic tool to complement antigen results for TAS-stopping decisions and possibly for post-elimination surveillance.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…16 In a recent seroprevalence study among migrant workers in Malaysia, BLF Rapid was positive in 19.6% workers from India (10/51), 12.6% from Nepal (13/103), and 7.1% from Myanmar (1/14). 7 In conclusion, the present study showed that BLF Rapid test is a highly sensitive and specific test for detection of bancroftian filariasis in areas not endemic for O. volvulus or L. loa. The encouraging evaluation results and the field-applicability make the test a potential diagnostic tool to complement antigen results for TAS-stopping decisions and possibly for post-elimination surveillance.…”
supporting
confidence: 49%
“…PanLF Rapid contains BmR1 and BmSXP test lines and is meant for use in areas with mainly brugian filariasis, but with possible co-occurrence of bancroftian filariasis, such as in Malaysia. 7,8 The concentration and purity of BmSXP used in PanLF Rapid is lower than that used in BLF Rapid. The higher protein concentration in BLF Rapid increases its diagnostic sensitivity, whereas the higher protein purity ensures a high diagnostic specificity.…”
mentioning
confidence: 99%
“…Bhd., Selangor, Malaysia), and the panLF (Reszon Diagnostics International Sdn. Bhd., Selangor, Malaysia) tests, based on BmSXP, BmR1, or a combination of both recombinant antigens, respectively [ 21 , 28 , 29 ]. In all, several filarial antigens have been produced as recombinant proteins and assayed for possible use in LF diagnosis.…”
Section: Recombinant Antigensmentioning
confidence: 99%
“…These infectious diseases included, toxoplasmosis (46.2%, working in Malaysia), 24 TB (7%, Saudi Arabia and 11%, Qatar), 14 40 TB meningitis (37.5%, Qatar), 18 diarrhoeal bacterial infection (26.6%, Qatar), 16 protozoan ova/cysts (13.7%), helminths (6.2%) and hookworms (4.3%, Qatar), 12 hepatitis E (74%, Qatar), 17 Brugian Lymphatic Filariasis (BmR1) (2.9%, Malaysia) and parasitic infection (BmSXP) (13%, Malaysia). 26 Moreover, prevalence of salmonella among Nepalese migrant food handlers (3.7% Malaysia), 28 mean knowledge of food cleanliness and hygiene (73.1%, Malaysia) and symptom of foodborne illness (18.4% Malaysia) 30 ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%